EFFECT OF OWNERSHIP OF BLOCKHOLDER, INTANGIBLE ASSETS, AND COMPANY SIZE ON COMPANY VALUE - Michelle Priscillia Putri; Lusy Lusy (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Company value is the basis for investors' views of the company's success rate in managing and allocating its resources. The purpose of this study was to determine the effect of blockholder ownership, intangible assets and company size on company value as proxied by Price Earning Ratio (PER). The object of this research is the food and beverage sub-sector manufacturing companies listed on the IDX for the 2016-2019 period. The analytical method used in this research is multiple linear regression analysis. The results showed that blockholder ownership had a positive and significant effect on company value, intangible assets had no effect on company value, and firm size had a positive and significant effect on company value. Simultaneously the independent variables in this study have a significant effect on the dependent variable. Keywords: Blockholder Ownership, Intangible Assets, Company Size and Company Value.